A convenient dynamic loading device for studying kinetics of phase transitions and metastable phases using symmetric diamond anvil cells. Issue 1 (2nd January 2018) - Cheng, Hu; Zhang, Junran; Li, Yanchun; Li, Gong; Li, Xiaodong; Liu, Jing
ABSTRACT: We have designed and implemented a novel DLD for controlling pressure and compression/decompression rate. Combined with the use of the symmetric diamond anvil cells (DACs), the DLD adopts three piezo-electric (PE) actuators and three static load screws to remotely control pressure in accurate and consistent manner at room temperature. This device allows us to create different loading mechanisms and frames for a variety of existing and commonly used diamond cells rather than designing specialized or dedicated diamond cells with various drives. The sample pressure compression/decompression rate that we have achieved is up to 58.6/43.3 TPa/s, respectively. The minimum of load time is less than 1 ms. The DLD is a powerful tool for exploring the effects of rapid (de)compression on the structure of materials and the properties of materials.